Damage detection of multi‐story shear buildings due to earthquakes by model updating method. Issue 4 (10th June 2016) - Zhang, J.Y.; Aoki, T.
Summary: In this paper, we present a novel model updating method for damage detection of multi‐story shear buildings during severe earthquakes. The story stiffnesses are explicitly presented in an incremental manner; this enables a simple and robust algorithm for the purpose of identification of the story stiffnesses. The estimated modal data, including natural frequencies and mode shapes of lower modes, are used in the proposed algorithm; moreover, sensitivity analysis of natural circular frequencies is incorporated to reduce possible errors. The story stiffnesses are identified by an iterative algorithm, and the window shift technique is adopted to present change of the story stiffness due to damages in the buildings during earthquakes. Numerical examples demonstrate that the proposed method is of high accuracy, even when the recorded responses are polluted by a relatively high level of (white) noises. Copyright © 2016 John Wiley & Sons, Ltd.